Facebook for dummies - Abram, Carolyn; Pearlman, Leah (Hoboken, New Jersey : Wiley Publishing Incorporation, 2010)
"Is everybody on Facebook except you? Change that with this friendly guide. These Facebook experts show you how to set up your Profile, protect your privacy, find friends and family members, learn what's happening in their lives, and keep them up to date on yours. You can even improve your business life with Facebook -- here's how!"--Back cover.
Getting Started with facebook -- Sharing your life on facebook -- Getting organized -- Delving further into facebook -- The part of tens. Series Title: --For dummies.
Includes index.
Keywords: FACEBOOK (ELECTRONIC RESOURCE)